Monitoring of histamine-induced calcium channel activity of a single cell using semiconducting carbon nanotube transistors - Pham Ba, Viet Anh; Ngoc Pham Van Bach,; Nguyen Viet, Khoa (Vietnam Journal of Science and Technology, 2023)
A method using transistors based on semiconducting carbon nanotubes were developed for the real-time monitoring of the electrophysiological responses of individual cells to histamine stimulation. Transistors with one or three floating electrodes were utilized to evaluate histamine-induced Ca2+ influx into Hela cells via the recording of the conductance changes of the transistors. The Ca2+ influx resulted from the activation of histamine H1 receptors embedded on the cell membranes by histamine, which generated a temporary negative potential at the gap between the cell and the transistor. Moreover, the antihistamine effects of chlorpheniramine on histamine-induced Ca2+ influx were also investigated by using a transistor including three floating electrodes. Especially, only a single transistor was applied to repeat the measurements of the responses of multiple Hela cells pretreated with chlorpheniramine to histamine stimulation. This allows us to acquire data without being suffered from device-to-device variations, implying our method would be a simple but powerful method for applications of nanoscale biosensors to electrophysiological studies.